Development of mathematical thinking test: content validity process / Nurul Akmal Md Nasir ... [et al.] - Md Nasir, Nurul Akmal; Singh, Parmjit; Narayanan, Geethanjali; Mohd Habali, Aisyah Hani; Rasid, Nor Syazwani (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
Validity is the extent to which an instrument measures what it is to measure. The instrument's validity is assessed by confirming the instrument's capability to measure the intended measurement. Content validity, face validity, construct validity, and criterion validity are the four forms of validity that are often discussed. Content validity is the degree to which a measurement tool reflects the measured content, which will justify the tool's validity. The importance of content validity in the instrument has made it an essential step in instrument development. Content validity is a vital criterion in designing and ensuring instrument development's success. Since content validity is essential in ensuring overall validity, content validation should be carried out in a structured manner based on evidence and best practice. This paper outlines a methodical strategy and a detailed content validation process for developing a mathematical thinking test. Seven evaluators were selected to review two sets of the mathematical thinking test. Three content validity measurements are applied to assess the items' validity in the tests: content validity index (CVI), kappa statistic and content validity ratio (CVR). Based on the results, the item content validity index (I-CVI) ranged from 0.857 to 1, and the scale content validity index (S-CVI/Ave) was 0.957. The Kappa statistics were also excellent since items ranged from 0.849 to 1.000. Content validity ratio (CVR) scores revealed that all items are the utmost critical by the content experts. Findings of the content validity study showed that all items in both mathematical thinking tests were deemed appropriate for assessing students' mathematical thinking